P623 The effectiveness and tolerability of Crohn's disease exclusion diet in adult Crohn's disease patients: a retrospective study. (21st January 2022) - Mahajna, H; Abu-Salah, R; Tzur, M; Kedar, N; Ben-Horin, S; Kopylov, U; Engel, T
Abstract: Background: Crohn's disease exclusive enteral nutrition (EEN), a dietary therapy which consists exclusively of liquid formula, was shown to be effective in the induction of remission in the pediatric population but limited by poor tolerability to avoiding oral food. Crohn's disease exclusion diet (CDED) is based on excluding certain food components that are thought to negatively affect the gut immunity, the gut barrier, and the microbiome. In children and young adults, CDED combined with partial enteral nutrition (PEN) were highly effective in inducing clinical response and remission. Despite the promising data regarding the tolerability and effectiveness of CDED in prospective trials, real world data, especially those conducted on adult patients' population, still lacks. Methods: This is a retrospective study of adult CD patients treated with CDED at a tertiary medical center (Sheba medical center, Israel). All included patients had active CD (Harvey Bradshaw index >4). The study endpoint was a composite outcome of clinical response (HBI decline of at least 3 points) or remission (HBI decline to below 5 points) at 6 week and at 12–18 weeks. Results: Overall, 40 patients who met the inclusion criteria were treated by CDED between year 2020 and 2021. 67.5% were females; mean age 29.5±13.3; mean disease duration 3.4±4.7 years; mean CRP 20.1±26.1mg/dl; mean calprotectin 599.4±510.5 mcg/g at study onset; At CDED initiation, 17 (42.5%) were bio-naive; 14 (35%) were under maintenance therapy with a biologic; for 15 (37.5%) patients, CDED was the first treatment for CD; eleven (27.5%) patients started CDED concomitantly with another treatment (7 with corticosteroids and 4 with biologics). Most (85%) of patients combined the CDED with partial enteral nutrition. Forty patients and 20 patients underwent a follow-up assessment at week 6 and 12–18, respectively. The mean HBI at the beginning of the study was 8.0±3.9 and declined to 4.5±3.0 and 3.7±2.9 at weeks 6 and 12–18, respectively. Twenty-six (65%) patients and 16 (40%) patients achieved the study composite endpoint by week 6 and 12–18, respectively. Four (10%) patients required corticosteroid treatment during the CDED treatment. Patients who achieved the study endpoint at week 6 had shorter durations of the disease (2.3±3.8 vs 5.6±5.4 years, P=0.03) compared to patients who didn't. No other significant differences were noted in disease characteristics and disease activity parameters between responders and non-responders. Conclusion: In a real-world setting, treatment with CDED (either exclusive or combined with an additional treatment) appears to be effective in treating adult CD patients but adherence to the diet remains a challenge. Further and longer-term real-world studies are warranted.